Best Reviewer Award (Years 2018 & 2019) - Zopiatis, Anastasios (My University, 2026)
Global Review of Research in Tourism, Hospitality & Leisure Management. Best Reviewer Award (Years 2018 & 2019). Global Business Research Journals (GBRJ), August 2020.
Keywords: Business and industry